Analisis Kinerja Keuangan Dan Pengelolaan Keuangan Perguruan Tinggi Di Indonesia - Bakhri, Saiful; Pertiwi, Novi Dian (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2024)
This research is to evaluate the financial system at a university which analyzes the performance of the financial system, the performance and financial management of a university so that it can be used as evaluation material that support better change, This research is descriptive research , the result of applying financial patterns that effective, good and effective performance system provide financial governance result that are in accordance with systematic financial patterns,aim to encourage a better and more efficient performance system thereby improving the quality and of service.